South Park: A Postmodern Reading of Its Characters and Plot - Petrus, Raluca-Andreea (AMERICANA E-journal of American Studies in Hungary, 2022)
From its first episode in 1997, South Park has re-invented itself through plot and characters, often employing satire, irony, and (self-criticism), devices commonly associated with Postmodernism. This article is the first part of a broader research endeavour entitled “A Postmodernist Transgressive Narrative. The Case Of South Park: Challenging The Establishment”, which seeks to consolidate the series’ status as a postmodernist work in progress. The current article introduces the reader to the South Park universe by examining academic and non-academic sources and statistics in order to establish essential details concerning the series. The analysis also evaluates relevant sources concerning Trey Parker and Matt Stone, the co-creators of the series, and about the results of their artistic endeavours, manifested in the series’ plot, settings, main characters and the messages they convey throughout selected episodes. Future analyses will employ Postmodernist methodologies and research upon a corpus that includes the following episodes: Pinkeye (1997), Chinpokomon (1999), and Quintuplets 2000 (2000).